Foreign aid donation and the donor countries’ economic growth: an empirical study of OIC member countries - Broni, Mohammed Yaw; Duasa, Jarita; Lacheheb, Zakaria; Abdul Samad, Sakinah (IIUM Press, 2025)
The Islamic worldview mandates Islamic countries to show benevolence, through foreign aid donations, towards their foreign counterparts experiencing poverty and deprivation. However, Islamic countries are faced with a possible conflict of interests in their attempt to show benevolence to their vulnerable foreign counterparts, and to pursue the achievement of economic growth concurrently. This study aims to investigate whether such a conflict of interests exist by estimating the impact of foreign aid donation on the donor countries’ economic growth, using Organization of Islamic Cooperation (OIC) member countries as a case study. The Generalized Method of Moments (GMM) technique was employed to analyze data of eleven OIC member countries spanning 2016 to 2020, based on an augmented Cobb-Douglas production model. The results indicate that foreign aid donation has no significant impact on the donor countries’ economic growth. Foreign aid policies of the respective governments should consider increasing the countries’ foreign aid expenditures, in order to assist many deprived countries whose economic sustainability depends on international development assistance